A HISTORICAL PERSPECTIVE OF EXERCISE IN MEDICAL RECOVERY - Mardare, Ioana; Moraru, Cristina Elena (Sport și societate, 2023)
It is essential to study the evolution of each science over time because it generates valid conclusions for both the present and the future. The research of the past represents the primary source of documentation and information regarding the perspectives of development in each field. This paper manifests a two-fold purpose. The first is to prove that the science of recovery by movement, though young in many respects, has a millenary existence with the most outstanding scientists contributing to its progress. Moreover, through this paper, I aimed to support a change in the paradigm regarding the place and mission of physical exercise as a theoretical and practical field of study. The second purpose is to point it out as a response to a social need, namely prophylaxis and treatment. Hence, it manifests as a field of the concrete, not of the abstract.